Always a lighthouse, toujours un homme: exploring non-literal translation techniques in video game localizations or the purposes of second language acquisition - Riggin, Patrick Franklin (Kansas State University, 2018)
Many recent video games feature complex narratives that contain increasing amounts of written and spoken language. There has thus been growing need for them to be localized into other languages; that is, translated and adapted for markets where languages other than the video game’s language of development are spoken. While the localization process shares many similarities with other projects of translation, because the primary goal of a video game is to be entertaining, video game localization teams are allowed certain creative liberties in translating video games in order to maximize entertainment for players in target markets. Non-literal translation techniques, including transposition, modulation, equivalence, and adaptation, are used to avoid mistranslating in-game language. However, Mangiron and O’Hagan identify in their 2006 analysis of the English localization of Final Fantasy X certain “transcreation” techniques that are used by localization teams in order to make video games more entertaining for players in other markets. These transcreation techniques include the addition of linguistic variation, the re-naming of in-game terminology, the re-creation of wordplay, “contextualization by addition”, and the deliberate use of regional expressions. These transcreation techniques not only serve to make the localized version of a video game more entertaining for a target market, but also make the gameplay experience more original for players in these markets. This study will analyze non-literal translation techniques and “transcreation” techniques in the French localization of BioShock Infinite: Burial at Sea Episode 2 to determine how these translation techniques may be used to maximize entertainment and to create a more original gameplay experience for francophone players, followed by a discussion of how video game localizations may be implemented in second language acquisition contexts for the purposes of exploring certain L2 linguistic and cultural phenomena.
Keywords: Localization; Translation; Second Language Acquisition; Video Games; BioShock